Atmospheric aerosols : characteristics and radiative effects - Ramachandran, S. (Physics professor) (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2018)
"This book includes basic knowledge and understanding on the characteristics of aerosols over the continent and oceanic regions, their composition, residence times, sinks and size distributions, and their effects in the radiative transfer and climate of Earth"--
Climate and aerosols -- Physical, optical and chemical characteristics of aerosols -- Measurements of aerosols: instrumentation, techniques and parameters -- Aerosols: radiative transfer and effects -- Aerosol-cloud interactions and aerosol-climate coupling -- Aerosol impact on atmosphere and climate, air pollution and air quality.
OCLC-licensed vendor bibliographic record.
Keywords: Atmospheric aerosols; Radiative transfer; Climatology; SCIENCE / Earth Sciences / Geography; SCIENCE / Earth Sciences / Geology; SCIENCE / Physics; SCIENCE / Earth Sciences / General; SCIENCE / Geophysics